NETWORK TECHNOLOGIES OF SYSTEMS CNS/ATM - Павлова, С.В.; Євтушенко, О.М. (Proceedings of National Aviation University, 2012)
The architectures of modern network technologies are considered. Trends in aviation network CNS / ATM are shown. Principles of digital networks and the possibility of their use for the construction of “Aviation Internet” are analyzed.